KORELASI ANTARA POSTUR TUBUH DAN CEDERA OLAHRAGA DITINJAU DARI ASPEK BIOMEKANIKA - Mahmuddin; Indry Natalia Tambunan; Carry Rafles Naibah; Wisron Situmorang; Aldo Rahmat Pakpahan; Putri Enjel Sitorus (JURNAL ILMU KEOLAHRAGAAN, 2025)
This study aims to analyze the relationship between postural deviations and an increased risk of sports injuries from a biomechanical perspective. The research method is a literature review, examining various research results and current scientific sources that discuss the biomechanical aspects of posture and its relationship to sports injuries. The analysis was conducted descriptively and comparatively with biomechanical theory, empirical findings, and corrective approaches based on biomechanical training and technology. The results of the study indicate that postural deviations significantly affect movement efficiency and body stability, which in the long term can increase the risk of injury, especially in the lower back, knees, and shoulders. From a biomechanical perspective, this relationship is explained by changes in forces, torques, the center of gravity, and imbalanced muscle activation patterns. Effective postural prevention and correction efforts include biomechanical evaluation using motion analysis, core and stabilizer muscle strengthening exercises, stretching of tight muscles, and neuromuscular and proprioceptive control training. These interventions can restore postural alignment, improve the body's mechanical efficiency, and reduce the risk of recurrent injury.